Stages of Institutionalization of the Middle East Confrontation - E. A. Stepkin (Vestnik MGIMO-Universiteta)
Book review of Gregory S. Mahler The Arab-Israeli Conflict: An Introduction and Documentary Reader, 2nd Edition. Routledge, 2018. 416 p.